Variabilitas Curah Hujan dan Suhu Udara serta Pengaruhnya Terhadap Neraca Air Irigasi di Daerah Aliran Sungai Ciliwung - Dwi Ariyani (Balai Teknik Irigasi, 2017)
Climate change is an issue that is being faced by the global community, which affects the variability of temperature and rainfall. An increase in air temperature may lead to a decrease in the dependable flow or availability of water. Related to this matter, this research aim to identify the trend of air temperature change and rainfall on water availability in Ciliwung Watershed for 30 years (1985 to 2015). Analysis of the increase in trend of climate variables is done by using Mann Kendall Trend Test method, water balance analysis using surplus deficit balance method, and water availability analysis using Mock method. The results showed no change in rainfall variability. The average temperature rose by 0.20C, the minimum temperature increased by 0.90C, and the maximum temperature rose by 0.80C over the last 30 years. Water availability decreased by 2 m3/s or by 2,000 l/s during the last 30 years. Water balance analysis then conducted using the maximum irrigation water demand at the intake of 8.46 l/s/ha and the irrigation area of Katulampa Weir which was reduced from 1,288 ha to 333 ha (1985 to 2015). The results of this analysis indicate that there is no water balance deficit for agricultural land in Ciliwung Watershed. The result of this research is expected to support the management of water resources in the upstream Ciliwung Watershed.